Degradation of imidacloprid via the activation of peroxymonosulfate and peroxydisulfate using a Fenton-sludge-derived Fe0/Fe3C composite - Lee, Youn Jun; Lee, Jong Min; Huang, Mingzhi; Park, Seong Jik; Lee, Chang Gu (Journal of Water Process Engineering, 2023)
The Fenton process is a commonly employed advanced oxidation process for industrial wastewater treatment. However, large volumes of iron-containing sludge are generated in the Fenton reaction, causing secondary pollution. In the present study, we report a Fenton-sludge-derived biochar (FSB) designed to degrade the neonicotinoid pesticide, imidacloprid (IMD) via activation of peroxymonosulfate (PMS) and peroxydisulfate (PDS). The effect of pyrolysis temperature on the transformation of the crystal phase and surface functional groups of samples was monitored using X-ray diffraction, Fourier transformation-infrared spectroscopy, and scanning electron microscopy. The use of FSB treated at 900 °C (FSB 900) containing the iron phase Fe0/Fe3C led to the highest IMD degradation efficiency with both PMS and PDS (92.7 ± 0.5 % and 100.0 ± 0.0 %, respectively; [IMD]0 = 20 mg/L, [persulfate]0 = 2 mM, [FSB]0 = 0.2 g/L, reaction time = 60 min). The main reactive species involved in IMD degradation via PMS and PDS activation using FSB 900 were identified with scavenger tests. The effects of solution pH and the additional anions on the performance of IMD removal efficiency were also investigated. This study provides insights into the recycling of solid waste derived from the Fenton process and the degradation of recalcitrant organic pollutants in wastewater.
Keywords: Fenton sludge; Neonicotinoid pesticide; Persulfate activation; Reactive species; Solid waste utilization